Traditional use of Dasylirion acrotrichum in the Construction of Floral Arches for the Festival of San Jerónimo, in Coatepec, Veracruz, Mexico - Torres-Martínez, Guadalupe; López Binnqüist , Citlalli; Silva Rivera , Evodia; Velázquez-Rosas, Noe (Ethnobiology Letters, 2020)
In Mexico, floral arches are commonly constructed as offerings in religious festivals. The plants required for fabrication of these arches are currently in great demand, which could affect the species involved. The objective of this study was to document the traditional management of Dasylirion acrotrichum (cucharilla) as used in the construction of floral arches during a festival of great religious and community significance held every year in Coatepec, Veracruz, Mexico. The construction method of floral arches was documented, and the possible repercussions of this practice on the wild populations of this species were analyzed. In Coatepec, the mayordomía is a non-rotational traditional organization system, through which each arch is produced. This system guides the construction activities of the floral arch, which are shared among different actors with various degrees of experience and responsibility. We reveal that between 250 to 270 plants (ultimately using around 60% of this number) are used to produce the main arch. Likewise, it was documented that during plant collection there are rules observed to avoid extraction of juvenile specimens, especially those that do not have the quantity or quality of leaves required. The social, ritual, and ecological basis of the mayordomía represent an opportunity to build a strategy aimed at regulating the extraction of culturally relevant plant species, and it can also help to improve collection techniques and to encourage sustainable management. That is why we argue that Dasylirion acrotrichum must be understood and studied from a systemic, interdisciplinary perspective.